PEMODELAN FAKTOR-FAKTOR YANG MEMPENGARUHI KEMATIAN IBU MELAHIRKAN DI JAWA TENGAH DENGAN ZERO INFLATED POISSON REGRESSION - Yusrina Ratna Annisa; Jajang Jajang; Agus Sugandha (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2021)
One of the targets of the Sustainable Development Goals (SDGs) is to reduce the maternal mortality rate by 2030. In reducing the maternal mortality rate, it is necessary to first study the factors that influence it. The number of maternal mortality rate in Central Java Province in 2018 was a discrete random variable that had a Poisson distribution and had many zero values. Generally, a model was used to counting data is Poisson regression model. However, the maternal mortality that has many zero values caused overdispersion. Therefore, Poisson model was not relevant in that case. In this paper, we used Zero Inflated Poisson (ZIP) model to overcome overdispersion caused by many zero values. The results of the research show that ZIP model can explained influence the number of maternal mortality. Based on this research, the factors such as provision of tablets, pregnant women who experience obstetric complications, and households with a clean and healthy lifestyle can explain the number of maternal mortality.